Fundamental Understanding of Magnetic Reconnection via Spiral CT Scan. III. Electron Agyrotropy and Temperature Anisotropy - H. S. Fu; Z. Wang; J. B. Cao (The Astrophysical Journal)
For the first time, we reveal the distribution of electron agyrotropy and electron temperature anisotropy around a reconnection X-line by using the spiral CT scan technique, which is a novel technique analogous to that in the hospital. This X-line was detected by the Magnetospheric Multiscale (MMS) spacecraft and has been widely believed to host a magnetic reconnection without a guide field. With the help of such an advanced technique, we find that: (1) the electron agyrotropy is weak in the magnetosheath-side inflow region, medium in the magnetosphere-side inflow region, and strong near the X point; (2) the electron temperature is isotropic near the current sheet center but is parallel-dominant in both the magnetosheath-side and magnetosphere-side inflow regions, with the anisotropy on the magnetosphere side more prominent than on the magnetosheath side. Quantitatively, the strongest electron agyrotropy is within a scale of 10 km (0.1 d _i ) around the X point. Interestingly, there is no enhancement of electron agyrotropy near the magnetosheath-side separatrix line. Both the electron agyrotropy and temperature anisotropy exhibit asymmetric distributions in the two inflow regions, providing different conditions for wave generation and instability growth, which may affect the reconnection rate.